Parauapebas: na capital do minério, expansão das atividades terciárias - Áthila Lima Kzam (Confins)
The central objective of the scientific investigation is to understand the intra-urban restructuring of Parauapebas due to the expansion of tertiary activities. From a methodological point of view, it carries out a survey of theoretical references on the subject and develops a qualitative and quantitative research with primary data from the Central Register of Companies, demographic censuses, public finances and the Annual Social Information Report of the Ministry of Labor. In the final part, through a multitemporal analysis of four images from the Landsat-TM sensor, it produces a map that confirms the mutations of the municipal urban area. The main conclusions indicate that, although mining remains the main productive activity, Parauapebas is not a simple urban nucleus to support mineral extraction in the Serra dos Carajás since it is also characterized by the expansion of consumption, commerce and the provision of services, activities that contributed to the creation of new areas of intra-urban centrality observed in its spatial structure.